In situ synthesis of magnetic CaraPVA IPN nanocomposite hydrogels and controlled drug release - Mahdavinia, Gholam Reza; Etemadi, Hossein (Materials Science & Engineering C, 2014)
In this work, the magnetic nanocomposite hydrogels that focused on targeted drug delivery were synthesized by incorporation of polyvinyl alcohol (PVA), kappa-carrageenan (Cara), and magnetite Fe3O4 nanoparticles. The magnetic nanoparticles were obtained in situ in the presence of a mixture of polyvinyl alcohol/kappa-carrageenan (CaraPVA). The produced magnetite-polymers were cross-linked with freezing–thawing technique and subsequent with K+ solution. The synthesized hydrogels were thoroughly characterized by transmittance electron microscopy (TEM), scanning electron microscopy (SEM), X-ray diffraction (XRD), thermal gravimetric analysis (TGA), Fourier transform infrared spectroscopy (FT-IR), and vibrating sample magnetometer (VSM) techniques. The dynamic swelling kinetic models of hydrogels were analyzed according to the first- and second-order kinetic models and were found that the experimental kinetics data followed the second-order model well. Drug loading and release efficiency were evaluated by diclofenac sodium (DS) as the model drug. The in vitro drug release studies from hydrogels exhibited significant behaviors on the subject of physiological simulated pHs and external magnetic fields. Investigation on the antibacterial activity revealed the ability of drug-loaded hydrogels to inactivate the Gram-positive Staphylococcus aureus (S. aureus) bacteria. The mucoadhesive properties of the hydrogels were studied and the hydrogels containing kappa-carrageenan showed good mucoadhesiveness in both simulated gastric and intestinal conditions. [Display omitted] •In situ synthesis of magnetic kappa-carrageenan/PVA nanocomposite hydrogel.•Low salt sensitivity of magnetic nanocomposite hydrogels was observed.•The release of diclofenac sodium from hydrogels was pH-dependent.•The release of diclofenac sodium from magnetic hydrogels was affected by external magnetic field.•The hydrogels containing carrageenan component showed high mucoadhesiveness.